A report on the Ghana country level inception workshop of the CGIAR Initiative on Aquatic Foods - Frimpong-Manso, Jack Pumpuni; Agyemang, Mary Kudom; Mapedza, Everisto D.; Buisson, Marie-Charlotte; Asmah, Ruby; Ahiah, Lawrence (International Water Management Institute, 2022)
Inception workshop of the Aquatic Foods initiative in Ghana held in September 2022. This workshop also aimed to convey multiple stakeholders and initiate cross-institutional collaboration for the uptake of aquatic food production in reservoirs.